A versatile all-optical parity-time signal processing device using a Bragg grating induced using positive and negative Kerr-nonlinearity - Phang, Sendy; Vukovic, Ana; Benson, Trevor M.; Susanto, Hadi; Sewell, Phillip (Springer US, 2015)
The properties of gratings with Kerr nonlinearity and PT symmetry are investigated in this paper. The impact of the gain and loss saturation on the response of the grating is analysed for different input intensities and gain/loss parameters. Potential applications of these gratings as switches, logic gates and amplifiers are also shown.